Odpowiedź :
Odpowiedź
Pierwsze i trzecie wyrażenie są poprawne
[tex]\boxed { \:\: cos^2x - sin^2x + cos \, x \:\: } \\\\\boxed { \:\: cos \,2x + cos \, x \:\: }[/tex]
Szczegółowe wyjaśnienie
[tex]\dfrac { d \: (sin \, x + tan \, x ) \, cos \, x } {dx} = cos^2x + \dfrac {1} {cos \, x} - sin \, x \, (sin \, x + tan \, x)[/tex]
bo
- (f(x) · g(x))' = f'(x) · g(x) + f(x) · g'(x)
- (f(x) + g(x))' = f'(x) + g'(x)
a dla funkcji trygonometrycznych jest
[tex]\dfrac { d \: sin \, x } {dx} = cos \, x\\\\\dfrac { d \: cos \, x } {dx} = - sin \, x\\\\\dfrac { d \: tan \, x } {dx} = \dfrac {1} {cos^2x}[/tex]
[tex]\dfrac { d \: (sin \, x + tan \, x ) \, cos \, x } {dx} = cos^2x + \dfrac {1} {cos \, x} - sin \, x \, (sin \, x + tan \, x) =\\\\cos^2x - sin^2x + \dfrac {1} {cos \, x} - sin \, x \, \cdot tan \, x =\\\\cos^2x - sin^2x + \dfrac {1} {cos \, x} - \dfrac {sin^2x} {cos \, x} =[/tex]
[tex]cos^2x - sin^2x + \dfrac {cos^2x + sin^2x} {cos \, x} - \dfrac {sin^2x} {cos \, x} =\\\\cos^2x - sin^2x + \dfrac {cos^2x} {cos \, x} =\\\\\boxed { \:\: cos^2x - sin^2x + cos \, x \:\: } =\\\\\boxed { \:\: cos \,2x + cos \, x \:\: }[/tex]